The Influence of Mid-East Sundanese Dialect (L1) in The Pronounciation of English Among English Department Students at Universitas Majalengka - Falahuddin, Mochamad Adnan; Saleh, Mursid; Wuli Fitriati, Sri (English Education Journal, 2019)
In a local society, it is still rare to find students who are able to speak English because Indonesian loves to use local language or Bahasa Indonesia. It causes different dialects that makes harder to speak English naturally. This research is to describe and explain the articulatory phonetics that is influenced by Mid-East Sundanese dialect.This research was a qualitative case study. The subjects of this study were 18 English department students of Universitas Majalengka academic year 2017/2018. The data were collected by using questionnaires, studentsâ€™ recording, observation checklist, and an interview.Based on the research data, it can be concluded that the negative transfer of L1 through vowel sounds was sound [Ã¦]. The students tended to replace the sound [Ã¦] with [ÊŒ], and [e] as well as sounds [É™ÊŠ] and [eÉ™] that replaced with sounds [ÊŒ], and [ÉœË]. While, the consonant sounds which negatively affected by L1 were [Î¸], [Ã°], [Ê§]. The students tended to replace the sound with [c], [d], [t], or [s]. Otherwise, L1 positively affected the cluster sounds [pr], [kw], [bl], and [str]. All of the students could pronounce them properly.Based on the findings, the mispronounced words mostly are caused by the lack of pronunciation practice. It helped them to improve and to evaluate their pronunciation ability. Since the students were able to recognize those words, then teacher facilitate them to practicing pronunciation.